PEMBUATAN EKOENZIM DARI LIMBAH KULIT BUAH NANAS PADA MASYARAKAT PEDULI LINGKUNGAN DI DESA CIGOMBONG, BOGOR - Rini Setiati; Qurotu Aini Besila; Dewi Syavitri; Pri Agung Rakhmant; Harin Widiyatni (Universitas Trisakti, 2023)
Eco enzyme is a product of organic waste derived from vegetables and fruits, fermented with sugar in a container and allowed to stand for three months to become an active solution. The use of eco-enzyme as a natural cleaning solution contributes to protecting the environment because it treats household-scale organic waste. The community service program aims to enhance Cigombong Village's potential with a community that cares about the environment that has been formed. The eco enzyme can be used to clean all areas of the house, clothes, vegetables, and fruits, fertilize plants, eliminate pests, and improve the quality of plants; the eco enzyme is also very effective in repelling plant pests. The eco enzyme can also be utilized to stimulate plant hormones to enhance fruit and vegetable quality and improve crop yields. Making eco enzymes can be done simply, using easily available equipment. The raw materials for eco enzyme consist of brown sugar, water, and fruit peel waste in a ratio of 1:10:3. The container used for the eco enzyme is a plastic jar with a lid. A training program for making eco enzymes from fruit and vegetable peel waste can protect the environment, increase community plantation yields and make Cigombong village a fruit tourism village.